Key Agri-Climatic and Socio-Economic Indicators for Cereal Production across the World - P, Kusuma Grace; Mohsin, Tanzina; Arhonditsis, George; Mirza, Monirul; Gough, William A. (International Journal of Environment, Agriculture and Biotechnology, 2019)
This research focuses on the identification of key indicators of climate change impacting the cereal crop yields for fourteen countries across the world employing the principal component analysis (PCA) and the linear scoring technique using the World Bank Data for the period 1961 to 2013 for all indicators for all the countries. The Climate Change Crop Performance Indices (CCCPIs) are generated for each country for the first time using both the climatological and socio-economic indicators. These indices are used for comparing and monitoring the relative crop performance during the study period. The locations under study included Canada and Mexico from North America; Argentina, and Cuba from Latin America; France, and Portugal from Europe; Iran, and Israel from Middle East; Liberia and Somalia from Africa; and Mongolia, Nepal, Myanmar, and Philippines from Asia. Based on the PCA analysis and underlying assumptions, the following list of key indicators are identified for each country: Canada: temperature, CO2e and LACP; Mexico, France and Israel: temperature, CO2e and RF; Argentina and Cuba: CO2e and RF; Portugal and Somalia: Temperature, CO2e, LACP and RF; Iran:temperature, CO2e, CY and RF; Liberia and Mongolia: CO2e, CY and temperature; Nepal: CO2e, CY and RF, and Myanmar and Philippines:temperature and CO2e;. These indicators provide a signal of the desirable or undesirable changes in climatological or socioeconomic parameters that have occurred or may occur in future in the above-mentioned countries. These key indicators might help even the technology developers, land managers and the policy makers to develop new strategies and formulate new policies.